Routine frozen section during pancreaticoduodenectomy does not improve value-based care - Abhineet Uppal; Wade Christopher; Trang Nguyen; Brooke Vuong; Stacey L Stern; Juan Mejia; Roshanthi Weerasinghe; Evan Ong; Anton J. Bilchik (Surgery in Practice and Science, 2022)
Introduction: Frozen section (FS) is often performed to confirm negative margins during pancreaticoduodenectomies (PD). This incurs significant cost, despite lack of evidence of survival benefit. We sought to determine the frequency of positive FS during PD, associated costs per positive margin identified, and association with locoregional recurrence (LRR) and overall survival (OS). Methods: A database of 526 PDs performed from 2014 to 2017 at a multi-institution integrated health-care system was queried. Charts and imaging were reviewed for systemic treatment, FS and PM results, pathologic stage, LRR and OS. Direct facility and professional costs for FS were determined from billing data. Cox proportional hazards for LRR and OS were performed. Results: 9.2% of all initial FS were positive. Average cost per FS was $148, with a cost of $1,538 per positive FS identified. Positive FS was not associated with LRR (HR 1.32, 95% CI: 0.50–3.52, p = 0.58) or median OS (25.9 vs 36.2 months, p = 0.38). Conclusion: Routine FS during PD is a low-yield test with significant associated costs. Positive FS was not associated with locoregional recurrence or overall survival. Routine FS does not provide substantial benefit for value-based care when performing PD.